Effect of processing on morphology of hydroxyapatites: Bioactive glasses and crystalline composites - McAdams J.; Bowman E.; Cullum B.; Arnold B.; Kelly L.; Choa F.S.; Singh N.B.; Su C.H.; Mandal K.D.; Singh S. (My University, 2025)
Recent studies on multinary oxides for applications as laser hosts and high dielectric capacitors have shown that processing at high temperature provides glassy or crystalline materials based on thermal treatments and cooling rates. Since hydroxyapatites are now subject of great interests due to their bioactivity, interest in producing soft and hard materials with glassy and crystalline nature by processing parameters has become very important. Crystalline materials by using Bridgman, Czochralski and flux growth methods are costly and require huge investment. We have observed that even low temperature solidification in organic flux produced oriented fibers. This organic treated material has different characteristics than in situ oxide materials prepared by sintering and grain growth. Examples of phosphate and silicate-based systems will be presented to demonstrate soft and hard materials. Effect of TiO2 and other hardening elements will be also reported. © 2019 SPIE. Downloading of the abstract is permitted for personal use only.